Research on the dynamic evolution and differential analysis of the development efficiency of China’s marine economic circles - Zhang, Lin; Yuan, Hang; Liu, Bangfan (Frontiers in Marine Science, 2025)
This study focuses on the economic development efficiency of China’s three major marine economic zones, aiming to explore their dynamic evolution rules and regional disparity characteristics, thereby providing theoretical foundations and practical guidance for promoting sustainable marine economic development. Based on panel data from 11 coastal provinces in China (2012-2021), the research employs a three-stage super-efficient slack-based measure (SBM) model with undesirable outputs to measure marine economic development efficiency Additionally, it uses Dagum Gini coefficient decomposition method to systematically investigate regional disparities and their sources, and applies the kernel density estimation to analyze dynamic evolutionary characteristics. The study reveals three key findings: First, compared with the first stage, the measured marine economic development efficiency of China in the third stage generally increases, yet the rankings of provinces change to varying degrees. Second, it exhibits significant “polarization effects” among the three marine economic zones, each displaying distinct developmental patterns and distribution characteristics. Third, there is substantial spatial disequilibrium across the zones, with inter - regional differences constituting the primary source of developmental imbalances. These findings not only clarify the spatial configuration characteristics of China’s marine economic development but also provide crucial evidence for devising differentiated regional development policies.